Genetic Variations in Key MicroRNAs are Associated With the Survival of Nonsmall Cell Lung Cancer. Issue 47 (November 2015) - Wu, Shuangshuang; Shen, Wei; Pan, Yun; Zhu, Meng; Xie, Kaipeng; Geng, Liguo; Wang, Yuzhuo; Liang, Yan; Xu, Jiali; Cao, Songyu; Xu, Wei; Chen, Bo; et al.
Abstract : Abstract: MicroRNAs (miRNAs) are a class of small, noncoding RNA molecules involved in carcinogenesis. It has been identified that genetic variations in miRNAs contribute to cancer risk, prognosis, and survival. In the present study, we investigated whether single nucleotide polymorphisms (SNPs) of several key miRNAs ( miR-184, miR-218, and miR-124 ) were associated with the prognosis of nonsmall cell lung cancer (NSCLC) in a clinical cohort study including 1001 cases. Cox proportional hazards regression models were used to estimate the hazard ratios (HRs) and their 95% confidence intervals (CIs). We found that 5 SNPs were associated with NSCLC survival (rs919968, rs3775815, rs4867902, and rs6122390 in an additive model: adjusted HR = 1.15, 95% CI = 1.02–1.29; adjusted HR = 0.78, 95% CI = 0.67–0.91, adjusted HR = 1.24, 95% CI = 1.09–1.41; adjusted HR = 1.21, 95% CI = 1.07–1.36, respectively; rs298206 in a dominant model: HR = 1.25, 95% CI = 1.05–1.49). Even after the Bonferroni correction, 3 SNPs remained significant (adjusted P  = 0.010, 0.010, and 0.032 for rs3775815, rs4867902, and rs6122390, respectively). Additionally, the combined analysis of these 5 SNPs showed a significant locus-dosage effect between number of unfavorable alleles (rs919968-A, rs3775815-C, rs4867902-G, rs6122390-A, and rs298206-T) and death risk of NSCLC ( P for trend < 0.001). A statistically significant multiplicative interaction was found between the genotypes of rs4867902 and surgical operation status ( P int  = 0.013). These findings indicated that genetic variations in miRNAs ( miR-184, miR-218, and miR-124 ) might be prognostic markers for NSCLC patients.